PENGARUH KEJELASAN SASARAN ANGGARAN, BUDAYA ORGANISASI, DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA (STUDI EMPIRIS PADA UNIVERSITAS RIAU) - Heptariani.Z, Susi; Rasuli, M.; Taufik, Taufeni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
This study aims to examine and analyze how muchinfluence the budget goal clarity, organizational culture and reportingsystem on performance accountability at the University of Riau. Thestudy was conducted on 54 people at the University of Riau budgetusers. Respondent participation rate amounted to 90.75% (49people). The analytical tool used is multiple regression with SPSSversion 21. Tests performed include testing the validity and reliability,testing normality of the data and the classical assumptions, thecoefficient of determination and hypothesis testing research. Theresults showed that the higher budget goal clarity and organizationalculture will affect to the higher of performance accountability.Meanwhile, no effect was found between reporting system onperformance accountability. The coefficient of determination was30.2%, where at least 69.8% change in the performanceaccountability is influenced by other factors not included in thisstudy.